2016
DOI: 10.4103/1793-5482.175646
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic bilateral basal ganglia bleed: A report of rare two cases and review of the literature

Abstract: Traumatic basal ganglia hemorrhage (TBGH) is relatively uncommon. Bilateral basal ganglia hematoma after trauma is extremely rare and is limited to case reports. We report two cases of traumatic bilateral basal ganglia hemorrhage and review the literature in brief. Both cases were managed conservatively. The general incidence of TBGH is reported between 2.4% and 3% of closed head injury. However, the incidence is higher in postmortem studies (9.8%). Bilateral traumatic basal ganglia hematoma is extremely rare.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Traumatic bilateral basal ganglia hemorrhage has rarely been reported. 11 Although our patient was found unconscious, she did not have any external signs of cranial trauma. Amphetamines in our patient's urine may predispose to ischemia or hemorrhage, however her CTA and MRA were negative for vasospasm.…”
Section: Discussionmentioning
confidence: 60%
“…Traumatic bilateral basal ganglia hemorrhage has rarely been reported. 11 Although our patient was found unconscious, she did not have any external signs of cranial trauma. Amphetamines in our patient's urine may predispose to ischemia or hemorrhage, however her CTA and MRA were negative for vasospasm.…”
Section: Discussionmentioning
confidence: 60%
“…Large size, associated coagulation disorders, DAI, presence of other bleeds like intraventricular of brain stem hemorrhage, age greater than 60, abnormal pupillary response, abnormal motor response to pain, and severe head injury are reported to be indicators for poor prognosis [3,7,8,18]. Kankane et al reported bilateral traumatic basal ganglia bleed and both the patient managed conservatively and outcome was good and no focal neurological deficit [19] Zhang YX, et al reported single case of 45 year female of traumatic bilateral traumatic basal ganglia bleed and patient managed conservatively and outcome was good and mild unilateral Hemiparesis [20] Willem Guillermo et al reported a 28-year old man, a victim of car-accident have hyperdense lesion in the basal ganglia bilaterally, with the presence of right parietal epidural hematoma. Craniotomy and epidural hematoma drainage were considered, associated to conservative management of gangliobasal traumatic contusions.…”
Section: Discussionmentioning
confidence: 99%
“…The general incidence of traumatic basal ganglia hemorrhage reportedly ranges from approximately 3% to 10%, and bilateral hemorrhage is even more rare. [ 17 , 18 ] The pathophysiologic mechanism of such hemorrhage has not been fully established; however, arterial tearing and stretching during the trauma may cause rupture of the perforators of various cerebral arteries including the anterior choroidal artery, middle cerebral artery, posterior cerebral artery, or microvasculature. Patients with traumatic basal ganglia hemorrhage have a relatively low incidence of skull fracture in contrast to the high incidence of other associated intracranial lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with traumatic basal ganglia hemorrhage have a relatively low incidence of skull fracture in contrast to the high incidence of other associated intracranial lesions. [ 17 , 18 ]…”
Section: Discussionmentioning
confidence: 99%